Intermediate Phases Formed During Synthesis Of β-Tricalcium Phosphate Via Wet Precipitation And Hydrothermal Methods - Othman, Radzali; Mustafa, Zaleha; Ishak, Nor Fatiha; Pham, Trung Kien; Shamsudin, Zurina; Mohd Rosli, Zulkifli; Mohd Noor, Ahmad Fauzi (Penerbit Akademia Baru, 2018)
Beta-tricalcium phosphate (β-TCP) was synthesized using an aqueous wet precipitation method as well as a hydrothermal method. The processing parameters adopted in both methods were maintained to be as similar as possible. The precursor materials reacted in both methods were 0.3 mole of phosphoric acid, H3PO4, and 0.45 mole of calcium hydroxide, Ca(OH)2. The available processing parameters for the precipitation method are much more varied whilst the parameters for the hydrothermal method are much more limited. Hence, the parameters chosen were based on the availability of the parameters to accommodate both methods, viz. the use of the same precursor materials in a stoichiometric ratio of 1.5, a reaction temperature of 70°C, a reaction time of 2 hours, a stirring speed of either 200 or100 rpm, and a stirring duration of 2 hours. The intermediate phases formed upon precipitation were compared. It was confirmed by x–ray diffraction that the powder formed from the precipitation method was monetite and hydroxyapatite, whilst the initial the powder formed from the hydrothermal method consisted of brushite and hydroxyapatite. Thermal analysis was performed on both powders to ascertain the best heat-treatment temperature. Both powders were subsequently subjected to a heat-treatment temperature of 900°C and both were confirmed by x-ray diffraction to be single-phase β-tricalcium phosphate. Scanning electron microscopy was performed on both heat-treated powders and the microstructures observed were found to be distinctly different. The precipitated powder consisted of nano-sized powders that were heavily agglomerated, whilst the hydrothermal powder consisted of a flattened microstructure due to the pressure imposed upon reaction.